2009
DOI: 10.1097/tp.0b013e3181a4bbf2
|View full text |Cite
|
Sign up to set email alerts
|

A Contact Lens-Based Technique for Expansion and Transplantation of Autologous Epithelial Progenitors for Ocular Surface Reconstruction

Abstract: Ex vivo expansion of ocular surface epithelium in the presence of autologous serum and transplantation with the aid of a soft CLs is a promising new technique capable of achieving ocular surface rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 39 publications
1
93
0
8
Order By: Relevance
“…The procedure was found to improve or to restore vision in a majority of the cases, and subsequent studies from other groups confirmed the potential of this new therapeutic approach [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 77%
“…The procedure was found to improve or to restore vision in a majority of the cases, and subsequent studies from other groups confirmed the potential of this new therapeutic approach [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 77%
“…24,25 For the past decade, it has been demonstrated that CLs provide an adequate reservoir for drugs and/or cells to adjust the environment of the cornea. It has been shown by DiGirolamo et al 25 that soft CLs can be used as a carrier for autologous epithelial cells to aid ocular rehabilitation in patients with unilateral LSCD, although this method is impossible with bilateral LSCD. Scleral lenses have been used by Espandar et al 24 to correct the inflammatory environment in the event of alkali burn in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Scleral lenses have been used as carriers of adipose-derived stem cells in a rabbit corneal epithelium repair model 24 and soft CLs have been used to deliver expanded epithelial cells to the cornea. 25 These characteristics make CLs ideal candidate carriers for the transfer of DPSCs or transdifferentiated DPSCs to an injured cornea.…”
mentioning
confidence: 99%
“…However, transfer of cells from the lens to the corneal surface was not conclusively demonstrated. 34 We used the same commercial siloxane-hydrogel contact lenses as control surfaces. We confirmed that corneal epithelium can be cultured on siloxane-hydrogel contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, none of the explants remained attached on OCT-only surfaces. The commercially available siloxane hydrogel contact lenses (Focus Night and Day lens [CIBA Vision]), which were used previously for the culture and transplantation of the corneal epithelium in human patients, 34 were used as positive controls and showed about 81% explant attachment.…”
Section: Polymer-coated Contact Lens For Corneal Epithelial Cell Tranmentioning
confidence: 99%